P PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP PEMAHAMAN KONSEP PESERTA DIDIK FASE E PADA MATERI EKOSISTEM DI SMA NEGERI 1 KUBUNG - Puspita, Widya Puspita Rahmah; Helendra; Yogica, Relsas; Olvia Rahmi, Fitri (Jurnal Biogenerasi, 2024)
Conventional learning methods dominantly used in schools, such as lectures, are less effective in helping students understand complex concepts, especially ecosystem material. This research aims to analyze the influence of the project-based learning model or Project-Based Learning (PjBL) on understanding ecosystem concepts in students at SMA Negeri 1 Kubung. Using a quantitative approach, this research applies a Quasi Experimental method with a Randomized Control Group Posttest Only design. The research results showed that the implementation of PjBL significantly increased students' conceptual understanding with the posttest average of experimental class students being higher than that of the control class. These findings indicate that the PjBL model is effective in increasing students' conceptual understanding of ecosystem material and can improve critical and collaborative thinking skills.